Influência da maltodextrina nas propriedades e na microestrutura da polpa de coco verde em pó - Araújo, Tayla Maria Ramos (2019)
This research aimed to evaluate the influence of maltodextrin on the properties and microstructure of green coconut pulp powder obtained by lyophilization. The physicochemical characteristics of the pulp used were determined. The best drying condition was chosen by means of a complete experimental design (DCCR), varying freeze-drying time and maltodextrin concentration and the influence of these variables on humidity, hygroscopicity, solubility and color parameters ( L *, a *, b *) of the powders. The powder in the best condition was physically and chemically characterized and its stability was analyzed for 90 days. In order to evaluate the influence of maltodextrin, powders containing 5.8 to 18% maltodextrin were evaluated by scanning electron microscopy, X-ray diffraction, flow indices, apparent densities, wall friction angles and isotherms sorption. The best condition obtained was 24.7 h of lyophilization and 11.9% maltodextrin concentration (m/m). The study of coconut pulp powder stability allowed to observe the increase of humidity, hygroscopicity and b * coordinate, decrease of L * and a * coordinates and solubility. For the adsorption isotherms of powders, the best fit model was the BET model with estimated average errors below 3.5%. The results of the flow index analyzes indicated that all evaluated coconut pulp powders were cohesive, although the 18% maltodextrin powder had a lower friction angle with the wall and higher apparent density. Scanning electron microscopy showed that the powders had irregular shapes, and as the concentration of the adjuvant increased, the surfaces became smoother and less crowded. In X-ray diffraction, the completely amorphous structure of these powders was demonstrated. It can be concluded that the addition of maltodextrin up to 18% improves all characteristics of the powder studied, but the powder with 11.9% adjuvant is still considered better because it does not need more maltodextrin and is largely satisfactory in maintenance and/or improvement of the characteristics studied.